Immobilized collagen prevents shedding and induces sustained GPVI clustering and signaling in platelets. (2nd January 2021) - Pallini, Chiara; Pike, Jeremy A.; O'Shea, Christopher; Andrews, Robert K.; Gardiner, Elizabeth E.; Watson, Steve P.; Poulter, Natalie S.
Abstract: Collagen, the most thrombogenic constituent of blood vessel walls, activates platelets through glycoprotein VI (GPVI). In suspension, following platelet activation by collagen, GPVI is cleaved by A Disintegrin And Metalloproteinase (ADAM)10 and ADAM17. In this study, we use single-molecule localization microscopy and a 2-level DBSCAN-based clustering tool to show that GPVI remains clustered along immobilized collagen fibers for at least 3 hours in the absence of significant shedding. Tyrosine phosphorylation of spleen tyrosine kinase (Syk) and Linker of Activated T cells (LAT), and elevation of intracellular Ca 2+, are sustained over this period. Syk, but not Src kinase-dependent signaling is required to maintain clustering of the collagen integrin α2β1, whilst neither is required for GPVI. We propose that clustering of GPVI on immobilized collagen protects GPVI from shedding in order to maintain sustained Src and Syk-kinases dependent signaling, activation of integrin α2β1, and continued adhesion.